The legend of Tolangohula: The forgotten female leader of Gorontalo before the European Colonial period - Magdalena Baga (Priviet Social Sciences Journal, 2025)
Folk tales, such as myths and legends, generally contain the wisdom of their people, which can serve as a reflection of constructing a society today. Generally, myths and legends in Indonesia feature women as important characters. In Indonesian myths and legends, women are often associated with the origin of places or the emergence of certain plants. The Gorontalo people have a legend about the first female leader in the region, Tolangohula. This female leader united small kingdoms under her authority. This research aims to reconstruct the existence of female leaders in Gorontalo in the past, which have been forgotten through the oral literature of the Gorontalo people. This reconstruction is expected to explore the role and values of female leadership in legends so that these leadership values can serve as a basic example for the formation of leadership character, especially in Gorontalo, through its rich oral literature. This reconstruction is also expected to demonstrate how Gorontalo society positioned women as leaders in the past. This study uses representation theory to demonstrate how female leaders are represented in Gorontalo’s folk legends. The oral tradition as history was employed in this study’s method. This method demonstrates that oral stories from the folk can serve as a benchmark for delving into the cultural history of a region that does not have a written tradition in their society culture. The findings demonstrate that the legends about female leaders were being forgotten from the interviews with some people in Gorontalo. The representation of female leaders through legends is positioned within the discourse after the colonial era. Despite this, the values of female leadership have left a legacy that aids in the development of a leader's character.